Promotion Strategy for Mudharabah Marhamah Savings Products at Bank of North Sumatra Syariah - Sri Riska Ananda Lubis; Nurainun Putri; Muhammad Lathief Ilhamy Nasution (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Islamic banks and conventional banks have different offering strategies. Islamic banks will provide offers while still applying the sharia principles of Mudharabah Marhamah Savings. There is one bank in North Sumatra that uses a mudharabah contract, namely Tabungan Marhamah. Therefore, it is important for customers to understand the use of the Mudharabah Marhamah Savings product facility at Bank Sumatra Utara so that it will have an impact on increasing the smoothness of transactions. The method used in this journal uses a descriptive method where data will be collected, compiled, grouped, analyzed and then applied so that it will become a clear and directed picture. The result of the research is that the offering strategy carried out by Bank Sumut Syariah Syariah Cabang Pembantu Lubuk Pakam can increase public interest in the Marhamah Mudharabah savings product.